Tamoio: Olha! Tem nó na cana - Ferrante, Vera Lúcia Silveira Botta [UNESP] (Universidade Estadual Paulista (Unesp), 1984)
O trabalho pretende reconstruir um movimento social ocorrido em uma usina da região de Araraquara, discutindo questões relacionadas a organização de luta, à atuação do sindicato e as manifestações de consciência dos participantes deste conflito.

The paper tries to reconstruct a social movement that look place in a sugar plant in the region near Araraquara. The idea is to discuss the problems related to the dispute organization to the union actuation and to the conscious manifestations of the insolved in the conflict.
Tamoio: sugar cane troubles
Keywords: Movimentos sociais; greve rural